Pesticide risk perceptions among bystanders of aerial spraying on bananas in Costa Rica - Barraza, Douglas (2020)
Little is known about how bystanders perceive risks from pesticide use in areas with frequent aerial spraying of pesticides. This research aims to better understand how bystanders (school workers) from three counties of the Limón province in Costa Rica, who did not have a contractual relationship with agricultural production, perceive risks of pesticides in the areas where they work and live. A face-to-face survey was carried out among 475 school workers, of whom 455 completed all 33 questions on pesticide risk perception. An exploratory factor analysis characterized underlying perceptions of pesticide exposure. Nine factors explained 40% of total variance and concerned severity and magnitude of perceived risk, manageability, benefits and support of pesticide use, amongst others. We subsequently analyzed what variables explained the five factors with satisfactory internal consistency, using separate multivariable linear regression models. Older school workers, (male) elementary teachers, and women school workers (particularly from schools situated near agricultural fields with aerial spraying of pesticides), felt greater severity and/or magnitude of risk from pesticide use. This study shows that bystanders are concerned about health risks from pesticide use. Their risk perceptions are not only shaped by gender and age like previously reported in the literature, but also by job title and geographical context. Understanding of what hazards people care about and how they deal with them is essential for successful risk management, bystanders should therefore be considered as a relevant actor in debates around pesticide issues and for informing the development of regulations and risk reduction strategies.